A comparative study on the effect of higher acrylate on cross-linkable PMMA used as environment friendly latexes. (March 2020) - Shukla, Sweta
The kinetics of emulsion polymerization of monomers methyl methacrylate (MMA)/ n -butyl methacrylate (BMA) was studied to investigate the effect of cross-linkable monomer poly(propylene glycol diacrylate) (PPGDA). The results showed that by the incorporation of PPGDA rate constant of reaction decreased. Fourier transform infrared spectroscopy and scanning electron microscope were used to characterize the synthesized polymers. The thermal analysis of samples was done by differential scanning calorimetry, and the results were compared by the previous studies with MMA/ n -butyl acrylate (BA) and MMA/2-ethylhexyl acrylate (EHA). The glass transition temperature ( T g ) values show that the latexes prepared using BA and EHA as comonomer was suitable for binder purpose, but in the present study the T g is not suitable in case of BMA as higher acrylate comonomer. That may be due to more cross-linking in MMA-BMA-PPGDA. The results conclude that the BA and EHA can be used as the binder, but the use of BMA is limited for the binder in coating applications.